2016
DOI: 10.1111/appy.12261
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing patterns of psychotropic medications and clinical features in patients with major depressive disorder with and without comorbid dysthymia in China

Abstract: There are important differences in the demographic and clinical features of comorbid dysthymia in Chinese MDD patients compared with previous reports. The clinical profile found in this study has implications for treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, the concordance of the CANMAT algorithm with naturalistic antidepressant treatment patterns in China has not been studied yet. Although previous studies reported the prescribing patterns of MDD in China ( Zhang et al, 2016 ; Chen et al, 2017 ; Feng et al, 2017 ), the longitudinal characteristics from initial pharmacotherapy to subsequent optimized treatment have not been described. Understanding the longitudinal prescription patterns especially optimized treatment strategies after the failure of monotherapy represents the first step to identify the gap between the CANMAT algorithm and real-world practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, the concordance of the CANMAT algorithm with naturalistic antidepressant treatment patterns in China has not been studied yet. Although previous studies reported the prescribing patterns of MDD in China ( Zhang et al, 2016 ; Chen et al, 2017 ; Feng et al, 2017 ), the longitudinal characteristics from initial pharmacotherapy to subsequent optimized treatment have not been described. Understanding the longitudinal prescription patterns especially optimized treatment strategies after the failure of monotherapy represents the first step to identify the gap between the CANMAT algorithm and real-world practice.…”
Section: Introductionmentioning
confidence: 99%